A new species of Litsea (Lauraceae) from Kerala part of Western Ghats, India - Robi, Aloor Jose; Udayan, Punnakkal Sreedharan; Li, Hsi-Wen; Li, Jie (Phytotaxa, 2017)
A new species of Litsea from India is described and illustrated. Litsea indoverticillata is recognized from the Malabar Wildlife sanctuary of Nilgiri phytogeographical zone of southern Western Ghats. It is distinguished from the closely related L. quinqueflora and L. verticillata by straggling shrub habit; 7–15 mm long, glabrous petiole, chartaceous and glabrous leaves, glabrous midrib; 15–24 pairs of lateral veins; solitary, glabrous, and pruinose inflorescence; greenish-white to whitish flowers.